(untitled) (Discourse of Law and Administration, 2023)
Clean Transport Zones are a novelty in Polish legislation. It is true that the formal possibility of introducing them should be bound by the Act of 11 January 2018 on electromobility and alternative fuels, nevertheless their actual establishment requires the adoption of an act of local law. Its proceedings are lengthy, hence only one such zone has been createds o far, in Krakow, in the Kazimierz district, but eventually it was abolished. In the initial text, the act was very strict, the emphasis was placed on zero emissions, hence the municipalities carefully used this instrument. The changes introduced in recent years, which can be considered significant, lead to the question whether the introduction of these zones should not be obligatory, as the deterioration of air quality is an objective value, or whether, as a result of flexibility, leave them optional.